Adsorption of copper (II) in aqueous solution using biochars derived from Ascophyllum nodosum seaweed. (May 2021) - Katiyar, Ravi; Patel, Anil Kumar; Nguyen, Thanh-Binh; Singhania, Reeta Rani; Chen, Chiu-Wen; Dong, Cheng-Di
Graphical abstract: Highlights: Copper (II) is nonbiodegradable pollutants and major source of environment pollution. Biochar showed effective removal of Copper (II) from aqueous phase. Biochar showed >99% removal efficiency with 223 mg g −1 Cu (II) adsorption capacity. Langmuir adsorption isotherm showed better fit of Cu (II) adsorption. Biochar could be an attractive bioresource alternative to costly adsorbents. Abstract: There has been growing research interest in exploiting biochar for cost-effective. removal of different pollutants. Heavy metals, especially copper II (Cu II) is highly toxic and nonbiodegradable pollutants, and has been major source of environmental pollution. In this study adsorption of Cu (II) on seaweed ( Ascophyllum nodosum )-derived biochar was systematically examined. The removal efficiency based on surface property of biochar and type of interactions associated with biochar produced at varying pyrolysis conditions were investigated. The highest removal efficiency of Cu (II) from aqueous media was >99% with 223 mg g −1 Cu (II) adsorption capacity observed by biochar derived at 700 °C and pH 5. Langmuir adsorption isotherm described the adsorption mechanisms of Cu (II) on biochar with cationic and anionic electrostatic attractions, surface precipitation, and pore depositions. Thus, this study shows that waste biomass (seaweed) could be a valuable bioresource for heavy metal remediation from various water bodies.